2014
DOI: 10.1002/hon.2147
|View full text |Cite
|
Sign up to set email alerts
|

Unique presentation of blastic plasmacytoid dendritic cell neoplasm: a single‐center experience and literature review

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and highly aggressive hematological malignancy derived from precursors of plasmacytoid dendritic cells. Very few cases of BPDCN have been described with lack of skin manifestations at the time of diagnosis. Here we report two rare non-cutaneous presentations of BPDCN without obvious skin lesions at our institution and also the literature review. Our first patient had a unique presentation of BPDCN confined to the sinonasal region with central nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
(54 reference statements)
1
10
2
1
Order By: Relevance
“…Previously known as blastic natural-killer lymphoma, agranular CD4+ natural killer cell leukemia, and agranular CD4 + CD56 + hematodermic neoplasm, BPDCN is now recognized as a distinct neoplastic entity among “acute myeloid leukemia (AML) and related precursor neoplasms” in the 2008 World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissue ( 1 6 ). BPDCN represents approximately 0.7% of primary cutaneous hematological malignancies and 0.44% of all hematological malignancies ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously known as blastic natural-killer lymphoma, agranular CD4+ natural killer cell leukemia, and agranular CD4 + CD56 + hematodermic neoplasm, BPDCN is now recognized as a distinct neoplastic entity among “acute myeloid leukemia (AML) and related precursor neoplasms” in the 2008 World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissue ( 1 6 ). BPDCN represents approximately 0.7% of primary cutaneous hematological malignancies and 0.44% of all hematological malignancies ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the typically sites of involvement, other unusual sites might be also affected. Paluri et al (2015) reported a patient diagnosed with a BPDCN confined to the sinonasal region and central nervous system (CNS). Although CNS is not typically considered a common site of involvement for BPDCN, a recent study has reported a frequent CNS involvement in their group of patients suggesting that the CNS might be a safe reservoir of blast cells in patients with leukemic presentation, due to the fact that drugs are unable to cross the blood-brain barrier (Martin-Martin et al, 2016).…”
Section: Clinicsmentioning
confidence: 99%
“…However, Voelkl et al (2011) reported an elderly patient with BPDCN with AML presentation and skin lesions who achieved a 26 month long remission after treatment with dose intensive multiagent chemotherapy. Long lasting remissions might occur in pediatric patients with good response to acute leukemia chemotherapy and allogeneic stem cell transplantation (Paluri et al, 2015;Male et al, 2010). Several studies have demonstrated that allogeneic stem cell transplantation following a reduced intensity conditioning (avoidance of highdose therapy) offers the best chance for long lasting remission, particularly when performed during the first complete remission, and suggests that this form of therapy should be pursued aggressively for all BPDCN patients (Dietrich et al 2011;Roos-Weil et al, 2013;Aoki et al, 2015).…”
Section: Prognosismentioning
confidence: 99%
“…Прогноз заболевания неблагоприятный [30,48,49]. Медиана общей выживаемости (ОВ) составляет 12-14 мес.…”
Section: результаты и обсуждениеunclassified